Hateship, friendship, courtship, loveship, marriage stories - Munro, Alice 1931- (Vintage Contemporaries, 2002)
A collection of short fiction explores the complexities of human relationships and emotions in stories about a housekeeper entering old-maidhood whose life is transformed by a practical joke and a lifelong philanderer who finds the tables turned.